'Between foods and medicines': A qualitative interview study of patient experiences of the meaning and usage of oral nutritional supplements. (1st November 2022) - Liljeberg, Evelina; Nydahl, Margaretha; Lövestam, Elin; Andersson, Agneta
Abstract: The aim of this study was to deepen the understanding of what oral nutritional supplements mean to patients and how this meaning connects to supplement usage, by exploring patient experiences of such supplements. Qualitative interviews were conducted in June 2019–March 2020 with ten patients with malnutrition or at nutritional risk, prescribed oral nutritional supplements by dietitians. Data were thematically analysed using systematic text condensation. Two final categories were identified: 'Oral nutritional supplements are a one-dimensional remedy' and 'Everyday oral nutritional supplement usage is regulated autonomously'. The patients described the meaning of oral nutritional supplements as nutrition. While the supplements could compensate for nutrients not eaten or be part of a helpful compensation strategy, they could not lessen the burden of altered eating. Supplement usage was described as dependent on the acceptance of taste and the priority given to nutrition in everyday life. Usage was greater when nutrients were perceived as needed, such as when striving for higher bodyweight or disease recovery. Usage was lower when a patient's own goals were not increased nutrient intake or bodyweight or when other activities were perceived as more important. Patient experiences indicated that oral nutritional supplements could serve as a remedy for malnutrition, but not for a situation of altered eating. Supplement usage was described as being regulated autonomously based on patient views on the importance of nutrition. Those views were diverse, highlighting the importance of supplement prescribers discussing treatment goals with each patient. A deeper understanding of the meaning of oral nutritional supplements and reasons for their usage from a patient perspective is crucial in order for healthcare to provide appropriate, effective nutrition therapy for malnutrition.